2009
DOI: 10.1111/j.1528-1167.2008.01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Clobazam in the treatment of Lennox‐Gastaut syndrome

Abstract: and yyOvation Pharmaceuticals, Inc., Deerfield, Illinois, U.S.A. SUMMARYPurpose: This randomized, double-blind, doseranging study evaluated safety and efficacy of clobazam (CLB) as adjunctive therapy for drop seizures in patients with Lennox-Gastaut syndrome (LGS). Methods: Sixty-eight patients with LGS aged 2-26 years were administered CLB (low dose = target 0.25 mg/kg/day; high dose = target 1.0 mg/kg/ day). The study consisted of 4-week baseline, 3-week titration, and 4-week maintenance periods, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 15 publications
4
126
1
4
Order By: Relevance
“…In children with Lennox-Gastaut syndrome, lamotrigine and topiramate is efficient in atonic and tonic clonic seizures and valproic acid is efficient in drop attack, atypical absence and myoclonic seizures (19)(20)(21). In studies performed in patients with Lennox-Gastaut syndrome, it has been reported that clobazamine leads to sedation with a lower rate, decreases seizures by 50-100% in more than 50% of the patients, maintains its efficiency of 42% after more than one year of use and provides seizure-free state for more than 6 months in 72% of the patients (22,23). It is reported that seizures of the patients with LGS are decreased with intravenous gammaglubulin treatment (24).…”
Section: Discussionmentioning
confidence: 99%
“…In children with Lennox-Gastaut syndrome, lamotrigine and topiramate is efficient in atonic and tonic clonic seizures and valproic acid is efficient in drop attack, atypical absence and myoclonic seizures (19)(20)(21). In studies performed in patients with Lennox-Gastaut syndrome, it has been reported that clobazamine leads to sedation with a lower rate, decreases seizures by 50-100% in more than 50% of the patients, maintains its efficiency of 42% after more than one year of use and provides seizure-free state for more than 6 months in 72% of the patients (22,23). It is reported that seizures of the patients with LGS are decreased with intravenous gammaglubulin treatment (24).…”
Section: Discussionmentioning
confidence: 99%
“…He is a candidate for palliative therapy with vagal nerve stimulation (VNS) 26 and also may benefit from clobazam therapy. 27,28 He may also cooperate with treatment with the ketogenic/Atkins diet. 29 An anterior (66% to 80%) corpus callosotomy is also a good option, and offers the greatest chance for substantial reduction in seizure frequency, especially for the tonic and atonic seizures, though it also has the highest morbidity of the treatments mentioned.…”
Section: 21mentioning
confidence: 99%
“…Лечение осуществляется с применением полите-рапии антиэпилептическими препаратами в макси-мально переносимых дозах [8,23,42,43]. Исходя из нашей практики, оптимальные комбинации в ле-чении СЛГ -вальпроаты + топирамат + сукцинимиды или бензодиазепины (клобазам).…”
Section: детской неврологииunclassified